Sistem Informasi Pelayanan Jasa Pencucian Mobil Dan Motor Pada Max Car Wash Berbasis Web - Kusuma, Aniek Suryanti; Sadiawan, I Wayan Gede (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2020)
Service is the provision of a performance or invisible action from one side to another side. One of the companies that focus on services is Max Car Wash, Max Car Wash is a company engaged in car wash and motorcycles services located at Jalan Raya Batubulan, Sukawati, Gianyar, Bali. Issues contained among the recording transactions are still on a note and ledger, the distribution of commissions to the staff is not maximum yet. In addition, the service to customers is less satisfactory seen from the behavior of some existing customers that can’t wait for his vehicle in the wash. Based on these problems, Max Car Wash needs a service system that is expected to assist in serving the process of payment transactions and recording commission staff each workmanship. In this system is also available queue booking feature, where customers can make a booking queue first. This study has been successfully built an information system service car and motor wash. This system aims to help the company by improving customer service and provide ease in obtaining the reports desired company.